“Aliansi Laki-Laki Baru”: The Role of Social Media in Promoting Gender Equality in Indonesia - Eni Maryani; Preciosa Alnashava Janitra; Detta Rahmawan (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2018)
A report from the United Nations Development Program (UNDP) in 2016 says that Indonesia is still struggling to close its gender equality gap. However, looking at the development of internet usage and the penetration of social media in Indonesia, it can be said that Indonesia has the opportunity to utilize social media to address various gender issues. This article uses a case study to explore and analyze the way “Aliansi Laki-Laki Baru” (ALLB) or “New Men’s Alliance”, a form of activism which emphasizes the importance of men's involvement in fighting for gender equality, utilizes social media to promote their ideas. As a social movement, ALLB consistently use social media to reach their audiences, engage their partners, and creating a sense of community. They focus in promoting mutual relationships between men and women and the importance of men’s involvement to support gender equality. The study on men’s involvement in promoting the agenda of feminism and gender issues is critical, yet there are still few studies in the context of Indonesia. This study shows that through ALLB, advocacy on gender issues has undergone a fundamental change that does not make women as the main focus but rather on men, and their role to fight for gender equality and justice for women.